Geological Modeling System Based on Flash3D Technology - Huang, Mu; Rong, Xiao Li (Applied Mechanics and Materials, 2013)
3D geological modeling is an inter-discipline subject applying computer technology to the geological research. With the development of Internet, 3D geological modeling based on Web has become a hot spot. In this article, we applied the Flash3D technology to the 3D geological modeling based on Web. We designed a process which use borehole data as original data source, automatic interpolation and identify strata from it, then calculate modeling data. We developed a 3D geological and geographical system based on Flex and Java platform using Flash3D engine technology. The system is a true 3D geological modeling software in B/S mode.